CONCEPÇÕES DE EDUCADORES SOBRE A PRODUÇÃO DO CURRÍCULO ESCOLAR NO ENSINO DE CIÊNCIAS. - Santos, Renata d. S.; Ferreira, Lisiane d. O.; Dobler, Guilherme H.; Rosa, Silvana K. D.; Peccin, Janessa C.; Frison, Marli D. (Salão do Conhecimento, 2013)
Resumo